A glossary of plastics terminology in 8 languages - Glenz, Wolfgang 1941-; Agassant, Jean-François; Celata, Claudio; Dihlmann, Christian; Linacisoro, Ibon; Ogay, Alexandr; Wang Daoyuan, David (Hanser, 2021)
This compact glossary in eight languages (English, German, Spanish, Italian, French, Portuguese, Russian, and Chinese) contains more than 2300 terms related to the chemistry, properties, testing, and processing of plastic materials. It was created to help bridge the language barriers within the international plastics manufacturing community. The concept is easy: a word-for-word translation without further explanation or interpretation. The glossary is particularly valuable for a quick reference of technical terms from a foreign language to the respective mother tongue and vice versa. Alphabetical indexes are included to make looking up terms fast and simple from any starting language. Even for translation of short technical texts or brochures, the glossary will be a helpful tool. The 8th edition includes approximately 300 new terms, and the addition of Portuguese as an additional language. The print edition also includes a code for a fully searchable electronic version available via download (Windows PC required)